Chain of Resistance in The Third Life of Grange Copeland - Chapagaee, Rajendra Prasad (Journal of Development Review, 2021)
Black women in America have been fighting not only against white patriarchy and white women’s racism but also against sexism within their own race. They have been victims of triple repression for being black on skin color, female in sex and economically underprivileged in patriarchal society. Being a black woman is totally different and harder than being just a white woman or a black man. They are bound with racial as well as cultural taboos and the interracial gender barriers. They are victimized not only by white male and female but also by their own men as slaves of slaves. They have been marginalized for being black and female. However, they fight against racial and patriarchal repressions with limited means especially with silence as a submissive woman but sometimes as a rebellious woman. They challenge the male-centered discourse to reclaim their lost identity of womanhood. The feminine gender norms like submissiveness, modesty, passivity disrupt and cease to disrupt according to situation and type of suppression upon them. They do not remain always silent recipients of violence and suppression but struggle with their womanist self to rebuild their selfhood. They create a discourse out of silence to explore subjectivity and start a journey from self- abnegation to self- recognition. While resisting the repressions, black women undergo inner development and maturation and transform themselves from their old narrow self to new open self. Their lives of the past are interconnected with present and construct their future. So black women are not always suspended victims of repressions but are capable to create a space for new generation to claim female identity and selfhood in the society